ZY‐3 Block adjustment supported by glas laser altimetry data. (1st March 2016) - Li, Guoyuan; Tang, Xinming; Gao, Xiaoming; Wang, Huabin; Wang, Yu
Abstract: ZY‐3 is the first Chinese civilian high‐resolution stereo‐mapping satellite, designed for 1:50 000 scale mapping. Although ZY‐3 has a very high accuracy for direct image geolocation without ground control points (GCPs), the use of some GCPs is still indispensable for stereo mapping. A novel method is proposed whereby spaceborne Geoscience Laser Altimeter System (GLAS) laser altimetry datasets are viewed as generalised height control points to support a ZY‐3 block adjustment. This method separates planimetric and height control, integrating the latter with GLAS data such that, without other GCPs, the vertical accuracy of ZY‐3 images can be improved significantly. Both flat and mountainous terrain were selected to evaluate the proposed method. The results show that by adding two GLAS height control points for a single image, or spaced every 50 km in the along‐track (orbital) direction for block images, the vertical accuracy can satisfy the requirements of 1:50 000 scale mapping, thus reducing the need for field surveying. Additionally, the method will be valuable for integrating spaceborne laser altimetry data and optical images for global mapping without any GCPs.